2020
DOI: 10.4149/gpb_2020013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of mouse testis uncovers cellular pathways associated with bisphenol A (BPA)-induced male infertility

Abstract: Quantitative proteomic analysis was performed using iTRAQ to explore the potential regulation of differentially expressed proteins (DEPs) by bisphenol A (BPA) in murine testis. BPA was intraperitoneally injected into mice at a dose of 100 mg/kg body weight for 7 consecutive days. After BPA treatment, the histopathology changes of testis were examined. The circulating levels of testosterone (T) and estradiol (E 2) were determined. iTRAQ was used to assess the expression levels of DEPs and to reveal potential in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This contradicts what was observed by authors such as Tian et al (2017) [ 69 ], who, after an oral BPA exposure (0, 100, 300 y 600 mg/kg BW/day) over 56 days in adult mice, reported disorders in spermatogenesis, lesions in the rough basal lamina of the seminiferous tubules and damage in the tight junctions between the Sertoli cells. Likewise, Jia et al (2020) [ 70 ] observed histological damage in testicular tissues of mice exposed to 100 mg/kg BW/day, noting that BPA significantly decreased spermatogenic cells in the seminiferous tubules, and they observed a large vacuolization within the latter. In consonance with these last two authors, Sencar et al (2021) [ 71 ] found serious degenerations such as testicular atrophy, spermatogenesis detention and interstitial oedema in the testicles of rats exposed during 28 days at concentrations of 100 and 200 mg/kg BW/day of BPA, demonstrating that only high exposure doses would originate the most serious effects in testicles.…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts what was observed by authors such as Tian et al (2017) [ 69 ], who, after an oral BPA exposure (0, 100, 300 y 600 mg/kg BW/day) over 56 days in adult mice, reported disorders in spermatogenesis, lesions in the rough basal lamina of the seminiferous tubules and damage in the tight junctions between the Sertoli cells. Likewise, Jia et al (2020) [ 70 ] observed histological damage in testicular tissues of mice exposed to 100 mg/kg BW/day, noting that BPA significantly decreased spermatogenic cells in the seminiferous tubules, and they observed a large vacuolization within the latter. In consonance with these last two authors, Sencar et al (2021) [ 71 ] found serious degenerations such as testicular atrophy, spermatogenesis detention and interstitial oedema in the testicles of rats exposed during 28 days at concentrations of 100 and 200 mg/kg BW/day of BPA, demonstrating that only high exposure doses would originate the most serious effects in testicles.…”
Section: Discussionmentioning
confidence: 99%